Biosafety and biodiversity risks - Smale, Melinda; de Groote, Hugo; Falck-Zepeda, José B. (International Food Policy Research Institute, 2006)
What is Biosafety Risk? The potential biosafety risks of transgenic varieties have generated controversy in the international community. According to the U.S. National Research Council (2002), these risks include (1) the flow of transgenes, (2) evolution of resistance in the targeted pest population, (3) plant escape and establishment of self-reproducing populations, (4) effects on nontarget species, and (5) health hazards (NRC 2002).